Indonesia HIMPUNAN SOFT FUZZY TRAPESIUM PADA PENGAMBILAN KEPUTUSAN: Fungsi Trapesium Himpunan Fuzzy Soft dalam pengambilan keputusan - Kholil, Muhammad (Equiva Journal, 2024)
This research introduces the concept of trapezoidal fuzzy soft sets as a new approach to decision-making under uncertain conditions. By combining the principles of soft set theory and fuzzy set theory, particularly trapezoidal fuzzy numbers, this concept enables a more objective representation of linguistic judgment. This research defines the basic operations, including complement, “AND,” and “OR,” in trapezoidal fuzzy soft sets and formulates a decision-making algorithm that incorporates weighted normalization and positive/negative ideal fuzzy objects. The approach is applied to Multi-Criteria Decision Making (MCDM) problems under fuzzy conditions, comparing it with traditional methods. Through detailed examples and theoretical proofs, this research demonstrates the advantages of trapezoidal fuzzy soft sets in capturing linguistic ambiguity and improving decision-making accuracy. Translated with DeepL.com (free version)